Marketing Communication Program Design of Online Travel Agent Kliktrip Using Benchmarking and Analytical Hierarchy Process Methods - Alviera Suci Damayanti; Sari Wulandari; Meldi Rendra (School of Industrial and System Engineering, Telkom University, 2021)
Kliktrip is an Online Travel Agent (OTA) that has trip & activities facilities and was established in2018 in Bandung. Kliktrip sales are still experiencing a decline due to low public awareness ofKliktrip which is seen through the number of downloads on mobile apps and Instagram followers.Kliktrip sales are still experiencing a decline and public awareness of Kliktrip is still low becauseKliktrip has not implemented 7 out of 8 marketing communication mix optimally. Therefore, researchwas conducted to design an effective marketing communication program for Kliktrip by usingbenchmarking and Analytical Hierarchy Process (AHP) methods. Based on the results of AHP dataprocessing, it can be seen that the selected benchmark partner is Explorer.id with a total priority vectorvalue of 0.44 and benchmark results with Explorer.id concluded that Kliktrip needs to increases thevalue of SEO, page views, and unique visitors on the website, creates a Tiktok’s account, webisode,and video podcasting, collaborates with cross-promotion, makes contests (giveaways), increase thenumber of downloads and reviewers on mobile apps, implementing mobile billboards and causerelated marketing, increasing customer service operational time, participating in exhibitions, andcollaborating with influencers.